A search for t (t)over-bar resonances with the ATLAS detector in 2.05 fb(-1) of proton-proton collisions at root s=7 TeV - Onofre, A. (2012)
A search for top quark pair resonances in final states containing at least one electron or muon has been performed with the ATLAS experiment at the CERN Large Hadron Collider. The search uses a data sample corresponding to an integrated luminosity of 2.05 fb−1, which was recorded in 2011 at a proton-proton centre-of-mass energy of 7 TeV. No evidence for a resonance is found and limits are set on the production cross-section times branching ratio to tˉt for narrow and wide resonances. For narrow Z′ bosons, the observed 95 % Bayesian credibility level limits range from 9.3 pb to 0.95 pb for masses in the range of mZ′=500 GeV to mZ′=1300 GeV. The corresponding excluded mass region for a leptophobic topcolour Z′ boson (Kaluza-Klein gluon excitation in the Randall-Sundrum model) is mZ′<880 GeV (mgKK<1130 GeV).